Tenant Liability for Breach of House Maintenance Clause in a Lease Agreement Based on Good Faith (Study in Gading Serpong) - Maria Eleos Tiurma Pakan (Universitas Negeri Semarang, 2026)
The ever-increasing demand for housing has driven the popularity of residential rental alternatives, yet in practice, these arrangements are often marred by challenges related to property maintenance. This study examines breaches of contract in residential lease agreements at the Topaz Cluster in Gading Serpong, where tenants have failed to maintain the building's physical condition and electronic facilities. The purpose of this research is to analyze the implementation of lease agreements from a civil law perspective and to examine the forms of tenant liability for maintenance breaches based on the principle of good faith. The methodology employed is empirical legal research with a qualitative approach. Primary data was obtained through interviews with homeowners and property consultants, as well as document analysis, while secondary data was collected through a literature review of relevant laws and legal literature. The results of the study indicate that the implementation of the agreement in the Topaz Cluster meets the validity requirements of a contract under Article 1320 of the Civil Code. However, the tenant was found to have breached the contract by neglecting maintenance obligations, resulting in structural damage exceeding normal wear and tear as well as damage to the provided electronic facilities. The dispute was resolved through non-litigation procedures. The tenant demonstrated post-contractual good faith by agreeing to cover all restoration costs with personal funds. The study concludes that the principle of good faith functions as an objective standard of conduct and a legal parameter in measuring the responsibility for performance.